PERANCANGAN SISTEM MONITORING DAN KONTROL KUALITAS AIR BERBASIS IoT PADA KOLAM IKAN AIR TAWAR - Riski Muhammad Natsir Nasution; Nazaruddin Nasution; Mulkan Iskandar Nasution (Universitas Riau, 2023)
Research has been carried out on designing an IoT-based water quality monitoring and control system in freshwater fish ponds, which aims to produce a tool that is able to monitor and control water quality remotely in freshwater fish ponds, to find out how the tool works in monitoring and controlling water quality over long distances in freshwater fish ponds. This research was conducted by connecting several components, namely using Arduino Mega 2560, WiFi expansion shield, pH sensor, turbidity sensor, DS18B20 sensor, ultrasonic sensor HC-SR04, and two DC pumps. Each sensor is compared with the actual measuring instrument and has an average percentage of error, the pH sensor is compared three times, namely the pH buffer solution of 4.01 with an average error of 2.1%, in the pH 6.86 buffer solution the average error is 0.4 %, and in aquadest solution the average error is 0.7%, the turbidity sensor has an average error of 1.6%, and the DS18B20 sensor has an average error of 0.4%. It can be concluded that the designed tool has been successfully made, and works well, for monitoring it is displayed on the LCD and in the Blynk application, for controlling water can be done through the Blynk application by turning on and off the pump that has been made.